Sustainability Reporting Model for Community-Based Household Waste Management Programs within the Global Plastics Treaty Framework - Komang Adi Kurniawan Saputra; Putu Ayu Sita Laksmi; I Wayan Werasmana Sancaya (PT Keberlanjutan Strategis Indonesia, 2026)
The global plastic pollution crisis prompted the formulation of the Global Plastics Treaty, which places reporting as a fundamental pillar of the agreement's effectiveness. However, the reporting mandate has been nationally oriented without accommodating community-based waste management initiatives at the local level. This study aims to develop a sustainability reporting model for community-based household waste management programs in Bali that aligns with the Global Plastics Treaty framework and the GRI 306: Waste 2020 standard. Using a qualitative approach with a case study design in several community-based programs in Bali, data were collected through in-depth interviews, observations, documentation studies, and focus group discussions with stakeholders. Data analysis used the Miles and Huberman interactive model. The study resulted in a multilevel reporting model with three levels of indicators: basic community-level indicators (waste volume, participation, managed waste, residue, income); intermediate indicators at the district/city level (per capita generation, recycling, waste reduction to landfill, economic impact); and advanced indicators at the provincial, national, and international levels (plastic consumption, waste leakage, GHG emissions) that align with the mandate of Article 15 of the Global Plastics Treaty. This research contributes to the sustainability accounting literature and provides operational guidance for communities and local governments in Bali. This model confirms that the effectiveness of the Global Plastics Treaty depends on the ability to bridge global mandates with local practices, making communities an integral part of the solution to the global plastics crisis.